Methane recovery from cassava starch wastewater via anaerobic digestion: Effect of inoculum source and kinetic study - Sawatdeenarunat, Chayanon; Saipa, Sasithorn; Suaisom, Pitchaya (Asia-Pacific Journal of Science and Technology, 2021)
The effects of inoculum sources on anaerobic digestion (AD) of cassava starch wastewater (CSW) were examined. Four different inoculums were used in this study, including the inoculum derived from anaerobically digested cassava starch wastewater (ADCS), pig manure (ADPM), cow manure (ADCM), and fresh elephant manure (EM). ADCS presented the highest methane potential of 351.04 NmL/g-volatile solid (VS)added. ADPM and ADCM derived from animal manures presented the lower methane potentials of 305.34 NmL/gVSadded and 329.95 NmL/ g-VSadded, respectively. EM showed the lowest methane potential of 239.43 NmL/gVSadded. Total chemical oxygen demand removal efficiencies showed the same trend with the methane potential and varied between 51.5% and 34.2%. The modified Gompertz equation well-fitted to the experimental data with R2 more than 0.99. The methane potential of ADCS was 343.41 NmL/ g-VSadded, which is not significantly different from the data obtained from the experiment. ADCS also presented the shortest lag phase of 3.75 days. Thus, ADCS could be the ideal inoculum for AD of CSW because of the good acclimation of the microorganisms to the substrate. However, when the availability of inoculum sources is concerned, the ADPM and ADCS could be the appropriate alternative inocula.